UI Design of Medical Check-Up Information System at Pratama Clinic Based on Design Thinking Method - Nana Misrina; Edi Supratman; Muhamad Ariandi; Maria Ulfa; Suyanto Suyanto (Universitas Bina Darma, 2022)
Medical Chek Up (MCU) or Periodic health checks are part of occupational health services that are the right of every worker and as part of preventing health risks to all workers and to reduce the risk of sudden death due to illness in the workplace, it is necessary to carry out annual periodic health checks as a worker obligation that must be carried out once a year. The purpose of this study was to design the User Interface (UI) of the Medical Check-Up Mobile application to make it easier for workers to find out the results of their examinations and doctors can evaluate the health status of workers. The object of this study was carried out at the Pratama Clinic of PT. Pertamina Patra Niaga Sub Holding Marketing Region Sumbagsel. The research method in this study is a descriptive method that is usually used to solve problems, by describing and describing the classified data. While the design method used is Design Thinking. The results of the User Interface design can later be used as a proposal to the Pratama Clinic of PT Pertamina Patra Niaga Subholding Marketing Sumbagsel Region for further implementation by the Internal IT Team.